PENINGKATAN LITERASI MEMBACA MELALUI TEKNIK STORY TELLING BERBASIS BAHASA IBU PADA SISWA KELAS V SDK MAJAMERE - Maria Magdalena Dhera; Kaka, Pelipus Wungo; Maria Desidaria Noge; Yohanes Vianey Sayangan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT This research aims to determine the results of applying mother tongue-based story telling techniques in increasing reading literacy in class V students at SDK Majamere. The type of research used is classroom action research (PTK) which consists of 4 stages, namely planning, action, observation and reflection. The subjects in this research were 19 grade V students at SDK Majamere and the object of the research was increasing reading literacy through story telling techniques based on their mother tongue. The data collection methods used in this research are observation, tests and documentation. In this research, a posttest instrument was used which was carried out in two cycles, namely cycle I and cycle II. Data was analyzed using quantitative data to determine the posttest results, while qualitative data was used to analyze the observation sheet. The results showed a significant increase from cycle I to cycle II. In cycle I the average class score was still low with an average of 40.27 and a completion percentage of 21.06%. In the implementation of cycle II, the results increased, namely a class average of 85.78 and a completion percentage of 78.94% with an increase in the class average from cycle I to cycle II of 45.51. Story telling techniques based on mother tongue can be said to be effective in increasing students' reading literacy and deepening understanding of the content of the texts they read.